A case report on Lassa fever and hearing loss: a rare occurrence and review of the literature. (2017)
Lassa fever is highly endemic in Nigeria and other West African countries, it is a disease associated with high case fatality and chronic sequelae in those that survived. Lack of effective vaccine has made the disease difficult to control and it prevention depends on eradications of the multmammate rats and universal precautions by all when a case is identified. We report a case of a 51 years old health worker who had a severe form of Lassa fever complicated by sensorineural deafness at the University College Hospital, Ibadan, South West Nigeria.